Tanshinone IIA inactivates Akt and induces caspase-dependent death in cervical cancer cells via the mitochondrial pathway - Hu Li; Yan Xu; Li Yang; Lei He (Bangladesh Pharmacological Society, 2015)
In human cervical cancer cells pro-apoptotic effect of tanshinone IIA isolated from the ethanol extract of Scutellaria barbata was investigated. Tanshinone IIA treatment resulted in apoptosis and mitochondrial membrane potential loss in the cervical cancer cells. The viability of SW756 and C4-1 cells was reduced in a concentration dependent manner on treatment with tanshinone IIA for 36 hours. Flow cytometric analysis in SW756 cells showed marked increase in accumulation of sub-G1-phase cell population. Tanshinone IIA treatment also caused significant increase in DNA fragmentation in these cells. DAPI staining revealed significant increase in nuclear condensation and apoptotic body formation on tanshinone IIA treatment in SW756 cells However, the effect of tanshinone IIA was reversed by caspase inhibitor, z-VAD-fmk. In tanshinone IIA treated cells Akt phosphorylation was markedly reduced and this decrease was inhibited by LY294002 (phosphatidylinositol-3'-kinase inhibitor). Tanshinone IIA treated apoptotic cells exhibited decrease in expression of Mcl-1. Thus tanshinone IIA induces apoptosis in cervical cancer cells through mitochondrial pathway.